A relational model of identity, symbolism, and representation in Soekarno-Era Monuments within the urban architecture of Jakarta (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Identity, symbolism, and representation constitute central themes in architectural and urban theory; nevertheless, their relational integration within the context of city architecture is frequently addressed in a fragmented and partial manner. This study seeks to develop a relational framework that connects identity, symbol, and representation through a focused analysis of Jakarta’s urban architecture during the Soekarno era. Five monuments are selected as case studies based on Toto’s (2014) classification, which characterizes monuments from the Old Order period as visual manifestations of Soekarno’s nationalist ideology. The research adopts a qualitative approach, employing a combination of literature review and visual analysis. The data are obtained from scholarly publications, visual documentation of the selected monuments, and historical records concerning their planning and construction. From a methodological perspective, the analysis investigates the architectural representations embodied in the monuments, interprets the symbolic meanings they convey, and identifies the identity narratives communicated through their forms and spatial expressions. The findings indicate that urban identity serves as the foundational basis for the production of symbols, which are subsequently materialized as representations of nationalism within Jakarta’s urban architectural landscape. This relational process is conceptualized as the Identity–Symbol–Representation (I–S–R) framework. The study contributes to the development of a conceptual framework for understanding the ways in which city identity is constructed, articulated, and communicated through architectural symbols and representational forms.
Keywords: Identity; Jakarta city architecture; Relation; Representation; Symbol